Analysis of a public space for youth use. The botellódromo in granada - Egea Jiménez, Carmen; A. Fabre Platas, Danú (Geografares, 2018)
This article analyzes the social construction of a public space, located in the city of Granada and frequented mainly by young people: the “botellódromo”. The main sources and tools of the research were the bibliographic and hemerographic survey and interviews with the regulars. The results indicate that the Spanish media highlight the most negative and sometimes “criminalizing” aspects of the activity. On the other hand, for the young people, attendance at this place means a ritual of passage to adulthood and university life, through leisure. Keywords: public space; youth; “bottellódromo”.